Toward waterborne protozoa detection using sensing technologies - Nemati, Sara; Shalileh, Farzaneh; Mirjalali, Hamed; Omidfar, Kobra (Frontiers in Microbiology, 2023)
Drought and limited sufficient water resources will be the main challenges for humankind during the coming years. The lack of water resources for washing, bathing, and drinking increases the use of contaminated water and the risk of waterborne diseases. A considerable number of waterborne outbreaks are due to protozoan parasites that may remain active/alive in harsh environmental conditions. Therefore, a regular monitoring program of water resources using sensitive techniques is needed to decrease the risk of waterborne outbreaks. Wellorganized point-of-care (POC) systems with enough sensitivity and specificity is the holy grail of research for monitoring platforms. In this review, we comprehensively gathered and discussed rapid, selective, and easy-to-use biosensor and nanobiosensor technologies, developed for the early detection of common waterborne protozoa.